1993
DOI: 10.1007/bf00186221
|View full text |Cite
|
Sign up to set email alerts
|

Ionomer-based bone substitute in otologic surgery

Abstract: During post-set hardening the self-curing bone substitute Ionocem develops a solid bond with the adjacent bony tissue, leaving no empty spaces. The fully matured material can be fixed to bone with freshly mixed cement or it may be used as a blank, e.g. an ossicular implant (Ionos ossicle). After insertion of 945 alloplastic middle ear prostheses over a period of 4.5 years, the take-rate was 94%. In some patients revision surgery became necessary, in 50% of cases because of prosthesis dislocation. A granular ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 2 publications
1
26
0
3
Order By: Relevance
“…Because of this, in vitro experiments cannot be substituted for carefully controlled long-range animal studies [5]. Although there are only a few reports of titanium for bone replacement in the middle ear [10,25], and a greater number of clinical applications of glass-ionomer cement [7][8][9], the clinical results correlate with the results of our animal study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Because of this, in vitro experiments cannot be substituted for carefully controlled long-range animal studies [5]. Although there are only a few reports of titanium for bone replacement in the middle ear [10,25], and a greater number of clinical applications of glass-ionomer cement [7][8][9], the clinical results correlate with the results of our animal study.…”
Section: Discussionsupporting
confidence: 81%
“…Glass-ionomer cement was first developed as a material in the field of dentistry, exhibiting good functional and biological results [6]. The use of glass-ionomer cement for middle ear prostheses is now widespread [7][8][9], but titanium is just now beginning to be used in human middle ear surgery [10].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last ten years they have also been developed for medical applications [2] and are now commercially available as a bone cement and as a pre-set cancellous bone substitute. They are the adhesive of choice for cementing cochlear implants [3].…”
Section: Introductionmentioning
confidence: 99%
“…In patients requiring revision of surgery, Geyer and Helms reported that half of the failures resulted from the displacement of prosthesis (8). However, there is no information about the character of bonding failures of bone cement ossiculoplasty.…”
Section: +mentioning
confidence: 99%